Design and Build 4G Open Radio Access Network at SmartLab Politeknik Negeri Jakarta - Lusi Damayanti; Damelia Panggabean; Sheren Regina Pingkan; Asri Wulandari; Alfin Hikmaturokhman; Adhi Hidayatullah (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The transition of RAN (Radio Access Network) development from the conventional model to Open RAN is motivated by the fact that Open RAN presents new services by reducing CAPEX (Capital Expenditure) and has the ability to integrate all cellular technologies in one server. One of cellular technology that can be developed using Open RAN is 4G LTE networks. The 4G LTE network produces internet with high data rate and low latency system. Various use case implementations can be carried out, for example to support learning on campus. In this study, the development of Open RAN 4G is implemented as a use case to build the Jakarta State Polytechnic SmartLab which produces its own cellular network. The importance of this research is to be able to ascertain the performance of the Open RAN 4G network using a Centralized RAN scenario. The method used in this research consists of knowing the problem, determining the tools used, determining the implementation scenario, configuring, and testing network performance. Parameters measured to test network performance are uplink downlink speed, RSRP value, and SINR value. Based on the scenarios that have been executed, the results show that the Open RAN 4G network has a maximum downlink speed performance of 13.6 Mbps, a maximum uplink speed of 7.22 Mbps, a maximum SINR of 22 dB, an RSRP of -200 dBm, and a maximum range that can be reached is 5 meters.